EFFECT OF ORGANIC MINERAL SUPPLEMENTATION ON BLOOD BIOCHEMISTRY, PLASMA ANTIOXIDANT ENZYME ACTIVITIES AND THEIR CORRELATION TO SPERM FUNCTIONAL CHARACTERISTICS IN OSMANABADI BUCKS - ARANGASAMY, A; J NAIDU, SHARANYA; HEMALATHA, K; SHARMA, RENU; SELVARAJU, S; KRISHNAIAH, M VENKATA; RANI, G P; BINSILA, B K; RAVINDRA, J P; RAGHAVENDRA, B (The Indian Journal of Animal Reproduction, 2022)
This study was carried out to investigate the effect of organic copper (Cu) and zinc (Zn) supplementation on blood biochemical parameters and antioxidant enzyme properties in growing Osmanabadi goats at the onset of puberty and semen quality. Forty bucks (five months) were allocated randomly into ten groups, all were fed with basal roughage and a concentrate mixture (50 : 50) supplemented (for a period of 8 months) either with different doses of organic Zn : 20 mg (T1), 40 mg (T2), 60 mg (T3), organic Cu : 12.5 mg (T4), 25 mg (T5), 37.5 mg (T6) and combination of Cu + Zn: 12.5 mg + 20 mg (T7), 25 mg + 40 mg (T8), 37.5 mg + 60 mg (T9), respectively, per kg dry matter (DM) or fed without additional mineral supplementation (Control). Blood samples collected on days 120 and 240 of treatment for analysis oftotal protein; albumin; cholesterol; high density lipoprotein (HDL) and glucose as well as enzyme activities like Catalase (CAT), Superoxide dismutase (SOD), Glutathione reductase (GR) and Glutathione peroxidase (GPx) were analyzed and correlated with spermatozoa functional characteristics. Significantly increased (P<0.05) enzymatic activities at days 120 and 240 were observed with positive correlations to the spermatozoa functional characteristics and enzyme activities. Varying level ofalbumin, glucose, HDL and protein in Cu treated groups of the experiment. Cu supplementation affects protein, glucose, HDL and albumin levels in goats; and supplementation of both organic Zn and Cu significantly increased the antioxidant defense enzyme activities in goats with positive correlation to sperm functional attributes.